PWE-103 Positive nutritional outcomes in patients receiving home parenteral nutrition (hpn) with palliative malignancy: a uk single centre series. (17th June 2017) - Whitefield, R; Iriarte, R; Bridgestock, H; Sothi, S; Burch, NE
Abstract : Introduction: HPN use in those with malignant bowel obstruction or palliative cancer is relatively commonplace. The 2009 ESPEN guidelines advise consideration if tumour related prognosis is 2–3 months, where TPN is expected to improve or stabilise performance status and/or quality of life. To review our practice we undertook a retrospective audit of all palliative HPN discharges over 4 years. Method: Retrospective audit of all palliative HPN discharges between October 2012 and November 2016 from UHCW. Data collected included: diagnosis, demographics, nutritional and biochemical parameters, estimated prognosis, complications, and outcome. Outcomes were collected up to 31 st January 2017. Results: 17 patients were identified; age 36–79 (mean 57); 59% female. Diagnosis included: malignant GI tract obstruction (n=12; 70%); malignant enterocutaneous fistulae (n=2; 12%); and malabsorption/autonomic dysfunction (n=3; 18%). Estimated prognosis was documented in 11/17 (65%):>3 months in 4 (36%); 3–6 months in 2 (18%);>6 months in 3 (27%), and >12 months in 2 (18%). 9/17 (53%) received chemotherapy alongside TPN. Weight at start of PN was 46.4–94.5 kg (mean 63.7); BMI 16.3–34.6 (mean 21.8); weight loss 0%–32% (mean 12.5%) prior to referral. 7/17 (42%) patients were alive at analysis. Of these, 3/17 (18%) had discontinued HPN due to resolution of intestinal failure, and 4/17 (24%) continuned HPN. Duration of HPN was 6.5–21 months (mean 13.4) in those with resolution, and 13.3–18 months (mean 15) in those continuing HPN. The remaining 10 patients (59%) had died; duration of HPN in this group was 0.3–29.1 months (mean 6.5). 12/17 patients (71%) survived longer than their estimated prognosis. Mean weight change on HPN was +8% (-12 to +39%). Starting grip strength was measured in 15/17 (8–33.9 kg; mean 18.7), and repeated in 11/17. It had improved in 91%; mean 4.7 kg (35.7%). 13 patients (77%) had anthropometric measurements at start of PN, and repeated in 9/17 (53%). Follow-up MUAC ranged from 5% decrease to 4% increase (average 0.2% decrease); 89% patients had a reduction in TSF (range −8.5% to +3.2%; mean 3.7% reduction); however MAMC had remained stable or increased in 7/9 patients measured (range −14.6% to +24.4%; mean +4.2%). Conclusion: Our results shows successful improvement in nutritional parameters and survival in patients managed on HPN with a palliative cancer diagnosis. Average survival on HPN was 9.7 months (294 days) with 71% surviving longer than their estimated prognosis. Grip strength improved in 91%. Although TSF thickness reduced and MUAC remained static despite TPN in the majority, MAMC increased highlighting that HPN resulted in gain of lean muscle mass despite their palliative cancer diagnosis. Disclosure of Interest: None Declared